The chimeric mitochondrial gene orf182 causes non‐pollen‐type abortion in Dongxiang cytoplasmic male‐sterile rice - Xie, Hongwei; Peng, Xiaojue; Qian, Mingjuan; Cai, Yicong; Ding, Xia; Chen, Qiusheng; Cai, Qiying; Zhu, Youlin; Yan, Longan; Cai, Yaohui (The Plant journal : for cell and molecular biology, 2018)
Summary D1‐cytoplasmic male sterility (CMS) rice is a sporophytic cytoplasmic male‐sterile rice developed from Dongxiang wild rice that exhibits a no‐pollen‐grain phenotype. A mitochondrial chimeric gene (orf182) was detected by mitochondrial genome sequencing and a comparative analysis. Orf182 is composed of three recombinant fragments, the largest of which is homologous to Sorghum bicolor mitochondrial sequences. In addition, orf182 was found only in wild rice species collected from China. Northern blot analysis showed that orf182 transcripts were affected by Rf genes in the isocytoplasmic restorer line DR7. Western blot analysis showed that the ORF182 product was localized in the mitochondria of the CMS line. An expression cassette containing orf182 fused to a mitochondrial transit peptide induced the maintainer line of male sterility, which lacked pollen grains in the anthers. Furthermore, the in vivo expression of orf182 also inhibited the growth of Escherichia coli, with lower respiration rate, excess accumulation of reactive oxygen species and decreased ATP levels. We conclude that the mitochondrial chimeric gene orf182 possesses a unique structure and origin differing from other identified mitochondrial CMS genes, and this gene is connected to non‐pollen type of sporophytic male sterility in D1‐CMS rice. Significance Statement D1‐ CMS rice is a sporophytic cytoplasmic male‐sterile rice developed from Dongxiang wild rice that exhibits a no‐pollen‐grain phenotype. We have cloned CMS gene orf182 in D1‐CMS lines and orf182 possesses a unique structure and origin differing from other identified mitochondrial CMS genes. Further dissection of the molecular mechanisms of orf182 will broaden our understanding of plant CMS, and this research will promote the widely use of D1 type hybrid rice.